E-ADA activity in serum of lambs experimentally infected with haemonchus contortus - Da Silva A.S.* (2013)
The aim of this study was to evaluate adenosine deaminase (E-ADA) activity in sera of lambs experimentally infected with Haemonchus contortus. We used 12 lambs divided into 2 groups; Group A had 5 healthy, non-infected animals (control) and Group B had 7 healthy animals infected with H. contortus. Lambs were infected orally with 500 larvae (L3) per animal every 2 days, for a period of 20 days, and later the infection was confirmed by examination of feces (eggs per gram [EPG] via fecal egg count). Blood collection was performed at days 0, 20, 40, 60, and 80 post-infection (PI) for analysis of E-ADA activity. Animals in Group A showed negative EPG throughout the experiment unlike those from Group B that had elevated EPG counts. E-ADA activity was reduced in the serum of animals infected with H. contortus when compared to non-infected controls at days 20, 40, 60, and 80 PI. Therefore, it is concluded that infection with H. contortus influences the E-ADA activity in lambs. © American Society of Parasitologists 2013.